Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

The Role of Benthic TA and DIC Fluxes on Carbon Sequestration in Seagrass Meadows of Dongsha Island - Lan-Feng Fan; En-Cheng Kang; Mariche B. Natividad; Chin-Chang Hung; Yung-Yen Shih; Wei-Jen Huang; Wen-Chen Chou (Journal of Marine Science and Engineering, 2024)
Coastal blue carbon ecosystems sequester carbon, storing it as plant biomass and particulate organic matter in sediments. Recent studies emphasize the importance of incorporating dissolved inorganic and organic forms into carbon assessments. As sediment-stored organic matter decomposes, it releases dissolved inorganic carbon (DIC) and total alkalinity (TA), both of which are critical for regulating the partial pressure of CO2 (pCO2) and thus carbon sequestration. This study investigated the role of benthic DIC and TA fluxes in carbon sequestration within seagrass meadows in Dongsha Island’s inner lagoon (IL) during the winter and summer seasons. Chamber incubation experiments revealed elevated benthic DIC and TA fluxes compared to global averages (107 ± 75.9 to 119 ± 144 vs. 1.3 ± 1.06 mmol m−2 d−1 for DIC, and 69.7 ± 40.7 to 75.8 ± 81.5 vs. 0.52 ± 0.43 mmol m−2 d−1 for TA). Despite DIC fluxes being approximately 1.5 times higher than TA fluxes, water pCO2 levels remained low (149 ± 26 to 156 ± 18 µatm). Mass balance calculations further indicated that benthic DIC was predominantly reabsorbed into plant biomass through photosynthesis (−135 to −128 mmol m−2 d−1). Conversely, TA accumulated in the water and was largely exported (−60.3 to −53.7 mmol m−2 d−1), demonstrating natural ocean alkalinity enhancement (OAE). This study highlights the crucial role of IL seagrass meadows in coastal carbon sequestration through net autotrophy and carbonate dissolution. Future research should explore the global implications of these processes and assess the potential of natural OAE in other coastal blue carbon ecosystems.

A generalized allometric model for predicting aboveground biomass across various bamboo species - Long-En Li; Tian-Ming Yen; Yu-Jen Lin (Biomass and Bioenergy, 2024)

An Integrated Framework with ADD-LSTM and DeepLabCut for Dolphin Behavior Classification - Shih-Pang Tseng; Shao-En Hsu; Jhing-Fa Wang; I-Fan Jen (Journal of Marine Science and Engineering, 2024)
Caring for dolphins is a delicate process that requires experienced caretakers to pay close attention to their behavioral characteristics. However, caretakers may sometimes lack experience or not be able to give their full attention, which can lead to misjudgment or oversight. To address these issues, a dolphin behavior analysis system has been designed to assist caretakers in making accurate assessments. This study utilized image preprocessing techniques to reduce sunlight reflection in the pool and enhance the outline of dolphins, making it easier to analyze their movements. The dolphins were divided into 11 key points using an open-source tool called DeepLabCut, which accurately helped mark various body parts for skeletal detection. The AquaAI Dolphin Decoder (ADD) was then used to analyze six dolphin behaviors. To improve behavior recognition accuracy, the long short-term memory (LSTM) neural network was introduced. The ADD and LSTM models were integrated to form the ADD-LSTM system. Several classification models, including unidirectional and bidirectional LSTM, GRU, and SVM, were compared. The results showed that the ADD module combined with a double-layer bidirectional LSTM method achieved high accuracy in dolphin behavior analysis. The accuracy rates for each behavior exceeded 90%.

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

Ultrasonography-Based Qualitative and Quantitative Evaluation Approaches for Pompe Disease - Yueh-Hui Lee; Hong-Jen Chiou; Da-Tian Bau; Dau-Ming Niu; Ting-Rong Hsu; Hsuan-En Huang; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to propose the qualitative and quantitative approaches to evaluate the skeletal muscle ultrasound images of 23 Pompe disease (i.e., acid maltase deficiency, AMD) patients and 14 normal subjects. Methods A cohort of 23 AMD patients and 14 normal subjects has been investigated. We compared the B-mode echo intensity of the rectus femoris muscle with that of its surrounding fat (subcutaneous fat) and proposed a qualitative grading method. Quantitative analysis of the region of interest (ROI) with the echo intensity and the segmented area was also performed. Results Qualitative results showed that AMD patients without clinical symptoms (without undergoing ERT) had the highest distribution of Grade 1, and AMD patients undergoing ERT had the widest distribution of Grade 2, and control group (n = 14) with the highest distribution of Grade 1. Using the segmented area approach, quantitative results showed that AMD patients undergoing ERT had the largest and widest distribution. Meanwhile the control subjects (normal subjects) had the lowest and the narrowest areas. The echo intensity of the segmented ROI of AMD patients undergoing ERT displayed the highest and widest (inhomogeneous) distributions. By contrast, the echo intensity of AMD patients without clinical symptoms was slightly increased and with low inhomogeneity. Conclusion The proposed ultrasonography-based qualitative and quantitative approach may be used to evaluate the severity of muscle destruction for AMD patients. Besides, the quantitative segmented area with regression analysis could help predict the incidence of onset of Pompe disease patients.

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

MAOA-VNTR Genotype Effects on Ventral Striatum-Hippocampus Network in Alzheimer’s Disease: Analysis Using Structural Covariance Network and Correlation with Neurobehavior Performance - Hsin-I Chang; Ya-Ting Chang; Shih-Jen Tsai; Chi-Wei Huang; Shih-Wei Hsu; Mu-En Liu; Wen-Neng Chang; Chia-Yi Lien; Shu-Hua Huang; Chen-Chang Lee; Chiung-Chih Chang (Molecular Neurobiology, 2019)

The effects of El Niño‐Southern Oscillation events on intertidal seagrass beds over a long‐term timescale - Hsing‐Juh Lin; Chen‐Lu Lee; Shang‐En Peng; Meng‐Chi Hung; Pi‐Jen Liu; Anderson B. Mayfield (Global Change Biology, 2018)
El Niño‐Southern Oscillation (ENSO) events can cause dramatic changes in marine communities. However, we know little as to how ENSO events affect tropical seagrass beds over decadal timescales. Therefore, a diverse array of seagrass ( Thalassia hemprichii ) habitat types were surveyed once every 3 months for 16 years (January 2001 to February 2017) in a tropical intertidal zone that is regularly affected by both ENSO events and anthropogenic nutrient enrichment. La Niña and El Niño events had distinct effects on the biomass and growth of T. hemprichii . During La Niña years, higher (a) precipitation levels and (b) seawater nitrogen concentrations led to increases in seagrass leaf productivity, canopy height, and biomass. However, the latter simultaneously stimulated the growth of periphyton on seagrass leaves; this led to decreases in seagrass cover and shoot density. More frequent La Niña events could, then, eventually lead to either a decline in intertidal seagrass beds or a shift to another, less drought‐resistant seagrass species in those regions already characterized by eutrophication due to local anthropogenic activity.

Catechol-O-Methyltransferase Val158Met Polymorphism on Striatum Structural Covariance Networks in Alzheimer’s Disease - Chiung-Chih Chang; Shih-Jen Tsai; Nai-Ching Chen; Chi-Wei Huang; Shih-Wei Hsu; Ya-Ting Chang; Mu-En Liu; Wen-Neng Chang; Wan-Chen Tsai; Chen-Chang Lee (Molecular Neurobiology, 2018)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Study of growth and body composition of red snapper Lutjanus erythropterus fed diets containing Escherichia coli expressing recombinant tilapia insulin-like growth factor-I - Wen-Liang LIAO; Hsin-Hui LU; Shun-Kuo HUANG; Jen-Leh WU; Jan-Hsiung HUANG; En-Chung LIN (Fisheries Science, 2008)